The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1161/circresaha.115.306223
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Tolerability of ACP-501, a Recombinant Human Lecithin:Cholesterol Acyltransferase, in a Phase 1 Single-Dose Escalation Study

Abstract: Rationale Low high-density lipoprotein cholesterol (HDL-C) in coronary heart disease (CHD) patients may be due to rate-limiting amounts of lecithin:cholesterol acyltransferase (LCAT). Raising LCAT may be beneficial for CHD, as well as for Familial LCAT Deficiency (FLD), a rare disorder of low HDL-C. Objective To determine safety and tolerability of recombinant human LCAT (rhLCAT) infusion in subjects with stable CHD and low HDL-C and its effect on plasma lipoproteins. Methods and Results A phase 1b, open-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 40 publications
2
55
0
1
Order By: Relevance
“…Recently, recombinant human LCAT (rhLCAT; ACP-501) was shown to be safe in a phase I study of subjects with stable cardiovascular disease 15 (ClinicalTrials.gov NCT01554800) and is being developed as a potential therapy for acute coronary syndrome. In this report, we describe the first-in-human use of enzyme replacement therapy (ERT) with rhLCAT in a patient with FLD and its effect on lipoprotein metabolism, and hematologic and renal function.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, recombinant human LCAT (rhLCAT; ACP-501) was shown to be safe in a phase I study of subjects with stable cardiovascular disease 15 (ClinicalTrials.gov NCT01554800) and is being developed as a potential therapy for acute coronary syndrome. In this report, we describe the first-in-human use of enzyme replacement therapy (ERT) with rhLCAT in a patient with FLD and its effect on lipoprotein metabolism, and hematologic and renal function.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, to test the feasibility of whether LCAT can be used as a potential therapy for reducing Lp‐X in cholestasis, we injected rhLCAT into WT mice treated with ANIT (Figures and ). Based on observations from previous clinical trials of rhLCAT, we hypothesized that the increased esterification of cholesterol by the infused rhLCAT would remodel Lp‐X into normal lipoproteins, as we observed in the LCAT‐Tg mice experiments. Figure A shows the baseline lipoproteins of WT mice (m1 to m6) by agarose gels stained with Filipin (Figure A, top) or Sudan black (Figure A, bottom), prior to ANIT treatment.…”
Section: Resultsmentioning
confidence: 89%
“…It can acutely lower Lp‐X, leading to the normalization of alkaline phosphatase, total bilirubin and AST. Based on the results of this study, rhLCAT, which has been shown to be safe in early stage clinical trials, could also be a potential therapy. rhLCAT is delivered by intravenous infusion and has a half‐life of several days, so it would be difficult to use as a chronic therapy, but it may be useful for the acute management of cholestatic patients.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations